Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1038/eye.1993.18
|View full text |Cite
|
Sign up to set email alerts
|

Orbital lymphomas and Castleman's disease

Abstract: A series of 100 consecutive orbitotomies for tumour was assessed. Lymphoid infiltrations contributed 27% and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 17 publications
0
12
0
2
Order By: Relevance
“…To the best of our knowledge, only three cases of lacrimal CD have been reported in the literature. Lacrimal gland biopsies in two of these three cases revealed that they corresponded to the hyaline vascular type, while a salivary gland biopsy of the third case revealed that the patient corresponded to the plasma cell type (22-24). Thus, it appeared unlikely that the lacrimal lesions were manifestations of MCD.…”
Section: Discussionmentioning
confidence: 88%
“…To the best of our knowledge, only three cases of lacrimal CD have been reported in the literature. Lacrimal gland biopsies in two of these three cases revealed that they corresponded to the hyaline vascular type, while a salivary gland biopsy of the third case revealed that the patient corresponded to the plasma cell type (22-24). Thus, it appeared unlikely that the lacrimal lesions were manifestations of MCD.…”
Section: Discussionmentioning
confidence: 88%
“…Without learning to read them we are, as Andrew Fleming has noted (in another context), "… semi-literate, in the face of a landscape which is there to be read and understood" (1998:3). Such maps establish essential context, and keeping them in view is critical to understand both the cultural associations of the features we study and the role of our own context in that process (see Snead 2012).…”
mentioning
confidence: 99%
“…Four cases of ophthalmic involvement have been reported in the literature [4-7]. Three cases reported orbital masses diagnosed as Castleman's disease [5-7], while the final case reported a serous retinal detachment along with choroidal thickening [4]. In our case, after combination chemotherapy for multicentric Castleman's disease, the serous elevation of the retina and the annular choroidal detachments of both eyes disappeared.…”
Section: Discussionmentioning
confidence: 60%